A Fast Autonomous Healing Magnetic Elastomer for Instantly Recoverable, Modularly Programmable, and Thermorecyclable Soft Robots. (4th June 2021) - Cheng, Yin; Chan, Kwok Hoe; Wang, Xiao‐Qiao; Ding, Tianpeng; Li, Tongtao; Zhang, Chen; Lu, Wanheng; Zhou, Yi; Ho, Ghim Wei
Abstract: Intrinsically self‐healing stretchable polymers have been intensively explored for soft robotic applications due to their mechanical compliance and damage resilience. However, their prevalent use in real‐world robotic applications is currently hindered by various limitations such as low mechanical strength, long healing time, and external energy input requirements. Here, a self‐healing supramolecular magnetic elastomer (SHSME), featuring a hierarchical dynamic polymer network with abundant reversible bonds, is introduced. The SHSME exhibits high mechanical strength (Young's modulus of 1.2 MPa, similar to silicone rubber) and fast self‐healing capability (300% stretch strain after 5 s autonomous repair at ambient temperature). A few SHSME‐based robotic demonstrations, namely, rapid amphibious function recovery, modular‐assembling‐prototyping soft robots with complex geometries and diverse functionalities, as well as a dismembering–navigation–assembly strategy for robotic tasking in confined spaces are showcased. Notably, the SHSME framework supports circular material design, as it is thermoreformable for recycling, demonstrates autorepair for extended lifespan, and is modularizable for customized constructs and functions. Abstract : A self‐healing supramolecular magnetic elastomer (SHSME) with a hierarchical dynamic network is developed to integrate fast autonomous healing (5 s to regain 300% stretch strain tolerance upon cut damage) and flexible magnetic maneuverability. The SHSME offers a circular material design framework for soft robots, as it is thermoreformable for recycling, autorepairable for extended lifespan, and demonstrates free prototyping for varying functions.